Pengaruh Lama Waktu Pengukusan Terhadap Karakteristik Kimia Dan Organoleptik Kaki Naga (Drums Stick) Ikan Marlin (Makiara Indica) Produk Koprasi Aceh Food Fish Jely - Lusi Harmoni; Anhar Rozi; Akbar Diansyah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Black marlin fish (makiara indica) or “balck marlin” it a class of Scombroid fish which is included in a fishery export commodity with high economic value in, dragon's feet is a processed fishery product whose research aims to de rermine the length of steaming time different and to find out the best chemical and organo leptic characteristics with different length of steaming time. quantitative research methods, data analysis used a completely randomized design (CRD) with 3 different treatments, P1: 15 minutes, P2: 30 minutes and P3: 45 minutes at 100 0C. Proximate analysis results, sho ing the best water content at 45 minutes with a value (61.35%), the best ash content at 15 minutes with a value (1.36%), the best fat content at 45 minutes with a value (3.01%), the best protein content at 15 minutes with a value (18.69%), the best crude fiber found at 15 minutes with a value (4.41%), and the best carbohydrate content at 30 minutes with a value of (9.58%). The organoleptic results that the analyst likes the most on appearance are in the 15-minute treatment with an average value of at least 7 (the spatial product is very strong), the taste that the analyst likes the most is in the treatment 30 minutes with an average value of at least 7, the most preferred odor by the analyst is in the 30-minute treatment with a minimum average value of 7 (the spatial product is less strong), and for the most preferred texture by the analyst is in the 30-minute treatment with a average of at least 7 (dense and compact).